Research on dynamic routing mechanism in network simulation - HAO Zhi-yu; ZHAI Jian-hong; YUN Xiao-chun; ZHANG Hong-li (Tongxin xuebao)
A fundamental requirement for any network simulation environment is the realistic forwarding of packets from a source to a destination in the simulated topology.The routing decisions will be affected by topology changes.In almost all current simulators,all the nodes know the topology changes instantaneously,which is obviously unrealistic.The model of dynamic routing was presented and analyzed.Further an approach was proposed to compute the time needed for each node to know the topology changes,and dynamic MTreeNix routing mechanism was presented,which maintains static routing table and a message queue of topology changes,and looks up routing states according to the known time of different changes.Experimental results show that our approach can improve the realism of dynamic routing in network simulation,with high simulation efficiency.